2021
DOI: 10.1002/lno.11954
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed pressure: Fluctuating impacts of multifactorial environmental change on a temperate macroalgal community

Abstract: Global change impacts marine organisms and communities mainly through ocean warming, acidification, deoxygenation, and changes in nutrient inputs and water circulation. To assess the ecological impacts of global change, the effects of multiple interacting environmental drivers, including their fluctuations, should be tested at different levels of biological organization. In an outdoor mesocosm study, we investigated the differential effects of three simulated upwelling events coupled with ocean warming (1-5 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Naturally, an interruption of a heatwave is most likely caused by a cold-spell during an upwelling event at which deeper and colder waters are shoaled to the surface (Lehmann and Myrberg, 2008;Wahl et al, 2021). Though, upwelling events in late summer are often hypoxic (Karstensen et al, 2014) and were shown to negatively impact A. rubens (Rühmkorff et al, unpublished data), they can still be beneficial when they interrupt lethal temperature extremes during heatwave events.…”
Section: Mitigated Impacts By Interrupted Heatwavesmentioning
confidence: 99%
“…Naturally, an interruption of a heatwave is most likely caused by a cold-spell during an upwelling event at which deeper and colder waters are shoaled to the surface (Lehmann and Myrberg, 2008;Wahl et al, 2021). Though, upwelling events in late summer are often hypoxic (Karstensen et al, 2014) and were shown to negatively impact A. rubens (Rühmkorff et al, unpublished data), they can still be beneficial when they interrupt lethal temperature extremes during heatwave events.…”
Section: Mitigated Impacts By Interrupted Heatwavesmentioning
confidence: 99%
“…Especially for perennial species, more attention should be paid to seasonal variations because both environmental baselines (i.e. means) and their distance to specific optima change with seasons (Ricart, Ward, et al, 2021; Wahl et al, 2021). These measurements require new technical developments in autonomous loggers and infrastructure (Pansch & Hiebenthal, 2019), as well as publication of best practice guides to standardize procedures (Lorenzoni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We highlight (iii) the importance of these specific chemical habitats in providing refugia against ocean acidification and deoxygenation but also (iv) point out how they can facilitate the resistance of populations or decrease species' fitness, depending on species’ capacities to respond to large abiotic fluctuations. We deliberately do not address in this review indirect hydrodynamic effects on shifts in species’ interactions and interactive impacts of multiple drivers fluctuating asynchronically (see Wahl et al, 2021 for instance).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of temperature stress is however important for the damage experienced by algae. Experiments done with bladderwrack Fucus vesiculosus (in 1500 L tanks in Kiel, in the western Baltic Sea) showed that in the early and late summer warming of 1 to 5 • C above ambient had mostly beneficial effects on bladderwrack, whereas in midsummer a similar warming had negative effects (Wahl et al, 2021). During midsummer, the heatwaves surpassed the physiological tolerance limits of the species, with detrimental effects on growth.…”
Section: Macroalgae and Vascular Plantsmentioning
confidence: 99%